Formation of forest mensuration indicators of Pseudotsuga menziesii (Mirb.) Franco in artificial plantations of the western region of Ukraine - Iurii Debryniuk; Stepan Myklush; Yuriy Myklush (Наукові праці Лісівничої академії наук України)
The plantations involving Pseudotsuga menziesii (Mirb.) Franco were studied in various forest-growth conditions of the Western Forest-Steppe, represented by different numbers of plots with varying participation of the studied tree species in the stand composition, ranging from 5% to 100%. The most widely represented in the conditions of the region are plantations with the participation of Douglas fir (Pseudotsuga) in the conditions of fresh fertile site type (D2), where 30 plantations were sampled. Therefore, the research results specifically pertain to these forest-growth conditions.